Business valuation : the ultimate guide to business valuation for beginners, including how to value a business through financial valuation methods - Shields, Greg ([Place of publication not identifed] : [publisher not identified], 2018)
Business Valuation: The Ultimate Guide to Business Valuation for Beginners, Including How to Value a Business Through Financial Valuation Methods contains real examples and talks about the "art" as well as the "science" of valuation. You'll also get a chapter that is focused on due diligence. Once you've listened to this audiobook, you should have a good handle on how to value a business. Maybe you won't be a highly paid McKinsey consultant, but you'll have what it takes to know what a business is worth, and you'll have enough smarts to avoid the obvious traps and pitfalls, such as "dressing up" profits. That can make the difference between selling your business at a price that funds your retirement and coming up short - or the difference between buying a great business at a good price or paying over the odds for a moribund company.
Business valuation :, Business